Novel method of polymer/low-melting-point metal alloy/light metal fiber composite fabrication - J. Park; K. S. Shin (eXPRESS Polymer Letters)
A novel method of polymer/low-melting-point metal alloy (LMA)/light metal fiber composite fabrication is proposed to solve problems of polymer/metal composites. The first step is mixing light metal particles with LMA at a temperature above the melting point of the LMA. The second step is cold extrusion of the LMA/light metal particles to fabricate LMA/light metal fibers. Thus, the LMA/light metal fibers with a density of ~4.5 g/cm3 were obtained. The last step is compounding a polymer with the LMA/light metal fibers at the processing temperature of the polymer above the melting points of the LMA. The effects of the length and the cross-sectional shape of light metal fiber on the morphology of the LMA/light metal fibers in the polymer matrix were studied, as were electrical conductivities and mechanical properties of the composites. As the length and/or the cross-sectional aspect ratio of the fibers was increased, the domains of LMA/light metal fibers formed more networks so that the electrical conductivity increased, and specific surface area of the domains increased so that notched Izod impact strength was improved. Thus, the polymer/LMA/light metal fiber composites were fabricated without degrading processability even at 60 vol% loading and the electrical conductivities over 103 S/cm were achieved.